2019
DOI: 10.1038/s41598-019-45426-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric signals of population decline in diademed sifakas occupying degraded rainforest habitat in Madagascar

Abstract: Anthropogenic habitat change can have varied impacts on primates, including both negative and positive outcomes. Even when behavioural shifts are seen, they may reflect decreased health, or simply behavioural flexibility; understanding this distinction is important for conservation efforts. This study examines habitat-related variation in adult and immature morphometrics among diademed sifakas ( Propithecus diadema ). We collected morphometric data from sifakas at Tsinjoarivo, Madagascar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…It should be noted that while P . diadema inhabit some fragmented forests, the long‐term viability of these populations is unknown as previous research has suggested that smaller habitats can lead to morphometric signals of population decline (Irwin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that while P . diadema inhabit some fragmented forests, the long‐term viability of these populations is unknown as previous research has suggested that smaller habitats can lead to morphometric signals of population decline (Irwin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At Berenty in the far south, P. verreauxi inhabits small degraded fragments that are associated with an abundance of protein-rich foods, potentially allowing this species to maintain relatively high densities (Norscia & Palagi, 2008). It should be noted that while P. diadema inhabit some fragmented forests, the long-term viability of these populations is unknown as previous research has suggested that smaller habitats can lead to morphometric signals of population decline (Irwin et al, 2019).…”
Section: Sifaka and Indri: Propithecus Spp And Indri Indrimentioning
confidence: 99%
“…Three studies included examinations of parasite load, with all reporting increased measures of parasitic infection with increased fragmentation ( E. collaris : Balestri et al, 2014; Lazdane, Broll, Theisinger, Bearder, & Donati, 2014; M. murinus : Raharivololona & Ganzhorn, 2009). While diademed sifaka ( P. tattersalli ) living in fragments were found to display signs of wasting in adults and stunting in immatures (Irwin et al, 2019) and to have lower white blood cell counts and zinc and iron levels, among other measures (Irwin, Junge, Raharison, & Samonds, 2010). Morphometric signals were most pronounced in fragment groups occupying the lowest quality home ranges, indicative of the importance of accounting for fragment disturbance (Irwin et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…While diademed sifaka ( P. tattersalli ) living in fragments were found to display signs of wasting in adults and stunting in immatures (Irwin et al, 2019) and to have lower white blood cell counts and zinc and iron levels, among other measures (Irwin, Junge, Raharison, & Samonds, 2010). Morphometric signals were most pronounced in fragment groups occupying the lowest quality home ranges, indicative of the importance of accounting for fragment disturbance (Irwin et al, 2019). Serum biochemical profiles by Junge et al (2011) additionally identified baseline trace mineral levels for indri ( I. indri ) living in close proximity to a proposed mine site.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the lack of direct, conflictive interactions (i.e., hunting or crop-raiding) between E. coronatus and the local Malagasy communities is likely another major factor supporting the proximity and cohabitation of these two populations (Missouri Botanical Garden, 2015;Mercado Malabet, 2017). has influenced the health of this population (Balestri et al, 2014;Irwin et al, 2019;Tecot, 2012).…”
Section: Discussionmentioning
confidence: 99%